Improving English Reading Comprehension Ability through Directed Activities Related To Texts (DARTs) Learning - Nurul Kamaliah; Triananda Putri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
The present research investigated the effect of using Directed Activities Related to Texts (DARTs) on reading comprehension among the students of secondary school. This research was conducted on class X students of Senior High School of Ummulqura Indonesia, Aceh with the number 25 students. This research was designed in the form of classroom action research. This research was done in two cycles. Then the instruments of this research were test field notes, observation check list and interview script. The data analysis uses both qualitative and quantitative descriptive approaches. The results showed that students' reading comprehension had significantly increased from an average value of 70.32 in the first cycle and 85 in the second cycle. Completeness of classical study in the first cycle is 52% and at the end of the second cycle was 80%. It showed that there was an improvement on the students' reading comprehension after applying the Directed Activities Related to Texts (DARTs) strategy during teaching learning activity.Brown, H. D, (2007), Teaching by Principles, New Jersey: Prentice HallMarpaung, A. P., Yanti, I., & Marzuki, Y. (2019).Developing Students’ Reading Comprehension Using STAD Strategy: A Classroom Action Research at SMA Negeri 7 Pekanbaru. REiLA : Journal of Research and Innovation in Language, 1(1), 10-16 https://doi.org/10.31849/reila.v1i1.2775Klingner, J. K., Vaughn, S., & Boardman, A. (2015). Teaching reading comprehension to students with learning difficulties, 2/E. Guilford Publications.Hameed, S. (2017). Effect of Intervention of Directed Activities Related to Text (DARTs) on Undergraduates’ Writing Skill. Pakistan Journal of Educational Research and Evaluation, 2(1), 77-103.Silitonga, S.A.R.Y, (2016). “The Effect of Applying Directed Activities Related to Text (DART) to Improve Students’ Reading Comprehension. Undergraduate Thesis. Medan. UMSU. Sugiarti, U. (2012). Pentingnya Pembinaan Kegiatan Membaca Sebagai Implikasi Pembelajaran Bahasa Indonesia. Jurnal Basastra, 1(1).Celce-Murcia, M. (2001). Teaching English as a second and foreign language, 3rd ed. Boston: Heinle and Heinle Thomson Learning Inc.Presetyo, W., & Abbas, M. F. F. (2017). The Use Of Questioning The Author (Qta) Strategy In Improving Students’ability In Reading Descriptive Text At The Seventh Grade Students Of Smp Islam Plus Jannatul Firdaus Pekanbaru. ELT-Lectura, 4(2)Mikulecky, B. & Jeffries, L (2004). More reading power. Pearson ESL. Ma’mur, I. (2006). Pijar-pijar pemikiran bahasa dan budaya. Jakarta: Diadit Media.Ulfianda, F. (2018). The Effect of Directed Activities Related to Text (DART) Method in Improving Students’ Reading Comprehension. Undergraduate Thesis. English Education Departement, Faculty of Teacher Training and Education. Medan: UMSU.Shamsulbahri, M. M., & Zulkiply, N. (2021). Examining the effect of directed activity related to texts (DARTs) and gender on student achievement in qualitative analysis in chemistry. Malaysian Journal of Learning and Instruction, 18(1), 157-181. https://doi.org/10.32890/ mjli2021.18.1.7Harrison, Colin. 2004. Understanding Reading Development. London: SAGEDavies, R. and Green, F. 1984. Reading for Learning in the Sciences. Edinburg: Oliver and Boyd.Zainab, K. (2012, November). Innovative approaches in teaching Science at secondary level: Focus on reading and writing in Science classrooms [Paper presentation]. Search of Relevance and Sustainability of Educational Change: An International Conference, at Aga Khan University Institute for Educational Development, Karachi, Pakistan.Supardi & Suharjo. (2012). Strategi Menyusun Penelitian Tindakan Kelas. Yogyakarta: ANDI Offset.Nunan, D. (2003). Practical English language teaching McGraw Hill/Contemporary.Purwanto (1996), Psikologi Pendidikan, Remaja Rosdakarya, BandungSyamsuar and Reflianto (2018) ‘Pendidikan dan Tantangan Pembelajaran Berbasis Teknologi Informasi di Era Industri 4.0’, Jurnal Ilmiah Teknologi Pendidikan, 2(2). doi: https://doi.org/10.24036/et.v2i2.101343.Trianto. (2009). Mendesain Model Pembelajaran Inovatif Progresif, Jakarta: Kencana Prenada Media GroupWahyuni, D. and Abdillah, D. (2019) ‘Analisa Pembelajaran Dan Penilaian Di Perguruan Tinggi Dengan Metode Student Centered Learning Berbasis Teknologi Informasi’, in Prosiding Seminar Nasional Era Industri (SNEI) 4.0, pp. 136–141.Rosyada, D. 2007. Paradigma Pendidikan Demokratis: Sebuah Model Pelibatan Masyarakat dalam Penyelenggaraan Pendidikan.Jakarta: Kencana Prenada Media Grup.Rouhani, Maryam and Behzad Pourgharib. (2013). The Effect of Games on  Learning Vocabulary.  International Research Journal of Applied and  Basic Sciences Vol, 4 (11):3540-3543 Science Explorer Publications.Richards, J. C. (2001). Curriculum development in language teaching. Cambridge: Cambridge University Press.